2006
DOI: 10.1007/s10495-006-0001-4
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-3 immunohistochemical expression is a marker of apoptosis, increased grade and early recurrence in intracranial meningiomas

Abstract: Caspase-3 is the ultimate executioner caspase that is essential for the nuclear changes associated with apoptosis. We investigated caspase-3 immunohistochemical expression in 58 primary intracranial meningiomas, using one monoclonal antibody detecting both precursor and cleaved caspase-3 (CPP32) and a second recognizing only the cleaved activated form (ASP175). Caspase-3 expression was analyzed in relation to baseline apoptosis-as illustrated by the expression of anti-single stranded DNA (ss-DNA), the antiapop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 39 publications
5
47
0
Order By: Relevance
“…In meningioma samples analysed a higher number of TUNEL-positive cells and a different amount of apoptotic signals have been detected compared to that observed by other authors [6,27]. Moreover a low amount of caspase-3 active form expression has been scored in grade II and III meningiomas.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In meningioma samples analysed a higher number of TUNEL-positive cells and a different amount of apoptotic signals have been detected compared to that observed by other authors [6,27]. Moreover a low amount of caspase-3 active form expression has been scored in grade II and III meningiomas.…”
Section: Discussionmentioning
confidence: 62%
“…In fact a malfunction of the apoptotic pathways leads to the setting of malignant tumors [3,4]. Presence of apoptosis has been frequently associated to recurrence and/or aggressive behaviour of meningiomas [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The activation of effectors caspases, like caspase-3, is an event also known as "point of no return" of apoptosis, beyond which the cells certainly will entry to apoptosis (Asselin et al 2001). The presence of CC3 has been demonstrated in many neoplasms, such as breast cancer, gliomas, neuroblastomas and sarcomas (Konstantinidou et al 2007, Kobayashi et al 2007, Matsubara et al 2008, Nassar et al 2008. Double inactivation of NF1 gene in Schwann cells seems to be the common event in neurofibromas and MPNSTs.…”
Section: Disease Free Survivalmentioning
confidence: 99%
“…In some tumors, i.e. meningiomas (Konstantinidou et al 2007), and Burkitt's and Burkitt-like lymphomas (Nomura et al 2008), the location of caspase-3 protein has been shown to be a prognostic marker. In a study with 41 sarcomas, but none MPNSTs, the overall and disease free survival were lower in cases of patients with higher levels of CC3 (Matsubara et al 2008).…”
Section: Disease Free Survivalmentioning
confidence: 99%
“…ISSN 2472-1158 that a high expression of CASP3 has been found associated with recurrence in meningioma [19,20], which might be due to the use of a fresh specimen instead of archival ones and inclusion of all the grade of meningiomas.…”
Section: Journal Of Clinical Epigeneticsmentioning
confidence: 99%